Prophylactic clip closure may reduce the risk of delayed bleeding after colorectal endoscopic submucosal dissection - Ogiyama, Hideharu; Tsutsui, Shusaku; Murayama, Yoko; Maeda, Shingo; Satake, Shin; Nasu, Ayaka; Umeda, Daisuke; Miura, Yoshio; Tominaga, Kouhei; Horiki, Masashi; Sanomura, Tamana; Imanaka, Kazuho; Iishi, Hiroyasu (Endoscopy International Open, 2018)
Background and study aims Endoscopic submucosal dissection (ESD) has a high en bloc resection rate and is widely performed for large superficial colorectal tumors, but delayed bleeding remains one of the most common complications of colorectal ESD. The aim of the present study was to evaluate the clinical efficacy of prophylactic clip closure of mucosal defects for the prevention of delayed bleeding after colorectal ESD.Patients and methods We enrolled consecutive patients with colorectal lesions between January 2012 and May 2017 in this retrospective study. In the early part of this period, post-ESD mucosal defects were not closed (non-closure group); however, from January 2014, post-ESD mucosal defects were prophylactically closed with clips when possible (closure group). The main outcome measured was delayed bleeding. Variables were analyzed using the chi-squared test, Fisher’s exact test, or Student’s t-test.Results Of 156 lesions analyzed, 61 were in the non-closure group and 95 in the closure group. Overall, delayed bleeding occurred in 5 cases (3.2 %). The delayed bleeding rate was 0 % (0/95) in the closure group and 8.2 % (5/61) in the non-closure group (P = 0.008). The mean procedure time for closure was 10.4 ± 4.6 min (range 3 – 26 min).Conclusions We demonstrated that prophylactic clip closure of mucosal defects might reduce the risk of delayed bleeding after colorectal ESD.